INOVASI DAKWAH DI ERA DIGITAL MELALUI MEDIA SOSIAL - Salim, Nur; Amanda, Nadia Cahaya; Rohman, Rohman (UIN Sulthan Thaha Saifuddin Jambi, 2024)
In the digital era, technology is very influential in almost all aspects of human life, including in the delivery of Islamic da'wah. Da'wah innovation in the digital era is very important to be able to reach a wider audience and bring a positive impact to society. Research and practice in the field of da'wah innovation are the key for da'wah to utilize technology wisely and effectively. The purpose of this paper is to discuss da'wah innovations in the digital era that can encourage the success of da'wah programs to be more effective. This paper also aims to provide insight for da'wah in utilizing technology more effectively and wisely. The method used in this article is to take data and information from several related literature, such as journals and books that discuss da'wah and technological innovations. The information is analyzed and presented in an easy-to-understand way to help readers gain a better understanding of da'wah innovations in the digital era. The results of this paper show that some of the da'wah innovations identified in the digital era include the use of social media to disseminate information and Islamic values, the use of virtual technology to organize da'wah events, and the use of digital platforms to rally support and donations for da'wah institutions. These da'wah innovations have a positive impact on a wider audience and help encourage the success of da'wah programs in a more effective way.